Analyzing The Effect of High Intensity Interval Training Among University Level Men Football Players - R, Ganesh; Mohanakrishnan, R.; V, Natesamurthy; Pranav Prakash, Prabhu; Sundararaj D, Syman (Journal of Neonatal Surgery, 2025)
Physical fitness is of paramount importance for football players due to the demanding nature of the sport. Football matches can be intense and last for 90 minutes or more. Players need high levels of aerobic endurance to maintain performance throughout the game. Football requires players to engage in physical contests such as tackling, shielding the ball, and competing in aerial duels. High Intensity Interval Training can be particularly beneficial for football players due to its focus on functional movements, strength, endurance, and agility. The study investigates the impact of High-Intensity Interval Training (HIIT) on specific physical and physiological attributes of university-level male football players. For this purpose, 30 male football players, aged 18 to 22 years, were randomly selected from SRM Institute of Science and Technology in Tamil Nadu, India. The participants were separated into two random groups: Group I, comprising 15 players, endured High-Intensity Interval Training, while Group II, also consisting of 15 players, served as the control group. Group I engaged in a single 60-minute training session per day, five days a week, for six weeks. Meanwhile, Group II did not follow any specialized training regimen but continued with their regular daily activities. Data on key physical and physiological parameters, including agility, flexibility, breath-holding time, and vital capacity, were gathered using standardized tests. Measurements were taken both before and after the training program to evaluate the selected variables. The dependent t-test and analysis of covariance (ANCOVA) were employed to analyze the pre- and post-test results for each variable separately. The findings revealed that the group undergoing High-Intensity Interval Training demonstrated significant improvements in the chosen physical and physiological characteristics. In contrast, the control group did not exhibit any notable enhancements in these measures.